2013
DOI: 10.21307/sjcapp-2014-014
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in Young Preschool Children with Symptoms of Attention-Deficit/Hyperactivity Disorder and Co-occurring Oppositional Defiant Disorder and Conduct Disorder

Abstract: Background: We have limited knowledge of the impact of attention-deficit/hyperactivity disorder (ADHD) symptoms on the daily functioning of young preschool children. Objective: This study investigated the level of impairment related to symptoms of ADHD in different functional domains. It also addressed how impairment caused by ADHD was related to ADHD subtype, symptom load, gender, and the cooccurrence of oppositional defiant disorder, conduct disorder, or both. Method: Participating children (N = 807) who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…We also found that symptoms of disruptive disorder and ASD are specifically related to ADHD diagnosis, as described by Antshel (2014) and Bendiksen, Svensson, et al (2014). Common neurobiological pathways and an underlying endophenotype between ADHD and ASD have been suggested by several authors (Christakou et al, 2013; Craig et al, 2015; Polderman, Hoekstra, Posthuma, & Larsson, 2014; Ronald, Larsson, Anckarsäter, & Lichtenstein, 2014).…”
Section: Discussionsupporting
confidence: 61%
“…We also found that symptoms of disruptive disorder and ASD are specifically related to ADHD diagnosis, as described by Antshel (2014) and Bendiksen, Svensson, et al (2014). Common neurobiological pathways and an underlying endophenotype between ADHD and ASD have been suggested by several authors (Christakou et al, 2013; Craig et al, 2015; Polderman, Hoekstra, Posthuma, & Larsson, 2014; Ronald, Larsson, Anckarsäter, & Lichtenstein, 2014).…”
Section: Discussionsupporting
confidence: 61%
“…The ADHD section of the PAPA concluded with an impairment section [ 28 ]. Whenever a parent reported at least one ADHD symptom, impairment was scored for six functional domains: (1) family relationships; (2) friends; (3) learning; (4) play/leisure activities; (5) child’s quality of life; and (6) family burden.…”
Section: Methodsmentioning
confidence: 99%
“…The functional domains gave a total impairment scale score (range 0–18), with Cronbach’s ɑ = 0.83. A sum score of three was equivalent to the 75th percentile for the participants who responded to the questionnaire at 5 years, in line with an earlier study of all participants at age 3 years old, and was taken to indicate a moderate level of impairment [ 28 ]. Thus, an impairment score of ≥ 3 was chosen as the threshold for impairment to be present.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies found a higher prevalence, severity or stability of DB in boys (Bendiksen et al 2014;Keenan et al 2011;Leblanc et al 2008;Wichstrøm et al 2012), whereas others observed only weak or no gender differences Basten et al 2015;Bufferd et al 2012;Wichstrøm et al 2012). In addition, sex differences did not always refer to the same DB in the different studies.…”
Section: Cohort and Association With School Adjustment In First Gradementioning
confidence: 98%
“…There is also evidence that the comorbidity observed in school age children is already present in early childhood (Bendiksen et al 2014;Bufferd et al 2012;Egger & Angold, 2006;Gadow & Nolan, 2002;Wichstrøm et al 2012). Moreover, preschool DB symptoms related to ADHD, ODD and CD have been associated with adjustment problems in the first years of school attendance (Brennan et al 2014;Campbell et al 2006;Cherkasova et al 2013;Lavigne et al 2001;Leblanc et al 2008;Shaw, Bell & Gilliom, 2000).…”
Section: Cohort and Association With School Adjustment In First Gradementioning
confidence: 99%